1992
DOI: 10.1093/carcin/13.5.783
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans as a promoter of oral mucosal neoplasia

Abstract: A model of oral mucosal carcinogenesis using the water-soluble carcinogen 4-nitroquinoline-1-oxide (4NQO) was combined with a model of oral mucosal candidosis to examine the ability of Candida albicans to promote the development of neoplasia in suitably initiated epithelium. Sprague-Dawley rats were initiated by the application of 4NQO to their palatal and tongue mucosa 3 times weekly for 4 weeks. The animals then received either application of a phorbol ester to act as a promoter, induction of experimental or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…796 SANO ET AL. TOXICOLOGIC PATHOLOGY in vitro (Williams et al 2001) and has been shown to have a promoter function in in vivo carcinogenesis studies (O'Grady and Reade 1992). Thus, the promoter function of C. albicans might be enhanced by the diabetic condition in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…796 SANO ET AL. TOXICOLOGIC PATHOLOGY in vitro (Williams et al 2001) and has been shown to have a promoter function in in vivo carcinogenesis studies (O'Grady and Reade 1992). Thus, the promoter function of C. albicans might be enhanced by the diabetic condition in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Hence a synergistic effect with candidosis and life-style factors may exist in oral carcinogenesis. Candida also efficiently converts ethanol into carcinogenic acetaldehyde (23)(24)(25). However, there are no studies showing that control of Candida would affect the incidence of oral cancer.…”
Section: -Infectious Agents • Bacterial Infectionsmentioning
confidence: 99%
“…Opportunistic infections and inflammation caused by C. albicans are associated with primary immunodeficiencies (PID) 4,5 , inflammatory disorders such as periodontitis 6,7 , Sjogren's syndrome, and salivary gland disease 8,9 , as well as oral squamous cell carcinoma [10][11][12] . C. albicans is a dimorphic commensal fungus that colonizes the mouths of 60% of healthy humans asymptomatically, yet it is the most common fungal pathogen causing infections when the host defense is weakened [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%